A comparative evaluation of the effect of three different concentrations of in-office bleaching agents on microhardness and surface roughness of enamel - An in vitro study - Khushboo Goyal; Suparna Ganguly Saha; Anuj Bhardwaj; Mainak Kanti Saha; Kaustubh Bhapkar; Shrija Paradkar (Wolters Kluwer Medknow Publications, 2021)
Background: To evaluate the changes in the micro-hardness and surface roughness of enamel treated with three different concentrations of in-office bleaching agents. Materials and Methods: In this in vitro study, 60 human incisors were divided into two groups (Group A and Group B). To obtain the baseline values, a Vickers tester was used to determine the surface microhardness in Group A, and a Surtronic tester was used for evaluation of surface roughness in Group B. Each group was then further subdivided into three subgroups and subjected to bleaching with Dash (Groups A1 and B1), Pola Office (Groups A2 and B2), and Opalescence Boost (Groups A3 and B3) containing 30%, 35%, and 40% hydrogen peroxide (HP), respectively. Samples were again subjected to testing to obtain the postbleaching values. Pre- and postbleaching data were analyzed by paired t-test. Intergroup comparison was carried out using one-way ANOVA (P ≤ 0.05). Results: A significant decrease in microhardness values was observed following bleaching in all the three groups, with Group A1 showing maximum percentage decrease (2.58%), followed by Group A2 (1.23%) and Group A3 (0.73%). Furthermore, an increase in surface roughness was observed following bleaching, with Group B1 showing maximum percentage increase (14.80%), followed by Group B2 (8.25%) and Group B3 (5.79%). However, there was no significant difference in either microhardness or surface roughness when comparing the postbleaching values among the three bleaching agents. Conclusion: In-office bleaching agents may adversely affect the microhardness and roughness of enamel surface which are not related to the concentration of HP used.